2006
DOI: 10.1890/0012-9658(2006)87[2411:cbrinf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Consumer–resource Body-Size Relationships in Natural Food Webs

Abstract: It has been suggested that differences in body size between consumer and resource species may have important implications for interaction strengths, population dynamics, and eventually food web structure, function, and evolution. Still, the general distribution of consumer-resource body-size ratios in real ecosystems, and whether they vary systematically among habitats or broad taxonomic groups, is poorly understood. Using a unique global database on consumer and resource body sizes, we show that the mean body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
685
7
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 611 publications
(745 citation statements)
references
References 22 publications
51
685
7
2
Order By: Relevance
“…These differences might indicate that in terrestrial ecosystems body mass is not as important for generating feeding hierarchies as it is in lake ecosystems. In Brose et al (2006) similar results have been found and it was hypothesised that this is due to physical and morphological constraints on trophic interactions. For example, if a lack of hard surfaces (as in pelagic systems) requires predators to consume their prey in one piece, gape limitation determines the maximal prey size.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These differences might indicate that in terrestrial ecosystems body mass is not as important for generating feeding hierarchies as it is in lake ecosystems. In Brose et al (2006) similar results have been found and it was hypothesised that this is due to physical and morphological constraints on trophic interactions. For example, if a lack of hard surfaces (as in pelagic systems) requires predators to consume their prey in one piece, gape limitation determines the maximal prey size.…”
Section: Discussionsupporting
confidence: 72%
“…If this one-dimensional niche space is anisotropic, species with a high position on the niche axis feed on those with a low position with a different probability than vice versa. Since in food webs it has been reported that predators are commonly larger than their prey (at least when parasites are excluded), body mass is indeed a useful proxy for niche position (Brose et al 2006).…”
Section: The Spectrum Of Ordered Three-node Substructuresmentioning
confidence: 99%
“…Therefore, the aspect of prey vulnerability most directly relevant to our study should concern the identity of predators the prey are vulnerable to, and therefore most likely to mob, rather than the modes of predator–prey interactions such as predator detection and escape, to which traits such as foraging technique and predator detection/escape strategy would have been more relevant (Lima, 1993; Sridhar et al., 2012). Functionally, body size fundamentally defines whether a species can be caught, subdued, and consumed by a given predator species (Brose et al., 2006; Cohen et al., 1993; Templeton et al., 2005), while foraging height determines the spatial overlap between prey and potential predators and thus prey exposure to and likelihood of encountering predators in forest ecosystems. These two traits thus represent the most relevant functional traits to the ecological context concerned in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we investigate how phylogeny can affect the relationship between consumer and resource body masses. In a recent paper, Brose et al (2006b) used a large data set and showed that the consumer body mass scales with resource body mass following a power law with an exponent significantly larger than one. This indicates that the gap between consumers' and resources' masses increases with body size.…”
Section: Introductionmentioning
confidence: 99%